2019
DOI: 10.20945/2359-3997000000115
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of metabolic syndrome in Brazilian soldiers

Abstract: Objective: The aim of this study was to carry out an epidemiological analysis of metabolic syndrome among Brazilian Army soldiers. Subjects and methods: Two thousand seven hundred and nineteen male soldiers of the Brazilian Army were evaluated from 2014 to 2016. Characteristics: age = 27.77 (± 8.59) years and BMI = 25.15 (± 3.41) kg/m 2. Blood tests and anthropometric measures were performed following the criteria of the International Diabetes Federation Task Force on MS Epidemiology and Prevention, 2009. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
1
9
0
6
Order By: Relevance
“…The multiple linear regression model was used to analyze the effect of covariables (criterion for MS) on ferritin values by the backward method. The coefficient of determination of the percentage of variation explained by the model was verified using R 2 . A logistic regression model was built to analyze the variables that contributed significantly to predict the outcome (hyperferritinemia) using the backward method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple linear regression model was used to analyze the effect of covariables (criterion for MS) on ferritin values by the backward method. The coefficient of determination of the percentage of variation explained by the model was verified using R 2 . A logistic regression model was built to analyze the variables that contributed significantly to predict the outcome (hyperferritinemia) using the backward method.…”
Section: Discussionmentioning
confidence: 99%
“…Several definitions of MS have emerged over the years, showing, however, some variations concerning the criteria and reference values of the metabolic parameters involved. [1][2][3][4] There are several diagnostic consensuses for MS, but most include cardiometabolic risk factors, such as obesity, dyslipidemia, high blood pressure, insulin resistance, and pro-inflammatory state. The National Cholesterol Education Program ATP III criteria (NCEP ATP III) require the presence of any three of the following five conditions: abdominal obesity, hyperglycemia, low levels of HDL-c, high levels of serum triglycerides, and high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…MS is the most common metabolic change and has a growing prevalence worldwide. [9][10][11] In Brazil, this condition, evaluated from the harmonization of international consensus and secondary analysis of the 2013 National Health Survey, showed that 8.9% (IC99% 8.4-9.5) of the Brazilian population has MS. 12 Recent data from an epidemiological analysis show that in a specific Brazilian population the prevalence of MS found was 12.21%. 13 The Brazilian Society of Cardiology infers that MS is this association of several cardiovascular risk factors that associated, in turn, to SAH, under the epidemiological view, is responsible for an increase of up to 2.5 times in mortality from cardiovascular events.…”
Section: Introductionmentioning
confidence: 98%
“…Neste contexto de DCNT, destaca-se a Síndrome Metabólica (SM) que em vista de seus elevados índices de prevalência mundial (Diaz, Espeche, March, Flores, Parodia, Genesio, Sabio, & Poppe, 2018;Assi, Ziv, & Dankner, 2019;Zhang, Qian, Sisi, Chuhao, & Hongzhuan, 2019), e que se estima, mesmo com escassez de dados epidemiológicos, a prevalência 8,9% nos brasileiros (Fortes, Rosa, Coutinho, & Neves, 2019), tornando-se um problema de grande magnitude, principalmente, devido à presença de resistência à insulina nas populações. O NCEP-ATP III coloca como necessário a presença de três entre cinco critérios para estabelecer o diagnóstico de SM.…”
Section: Introductionunclassified